Chimaerism shown by cytogenetics and DNA polymorphism analysis. Issue 10 (October 1994) - Green, A J; Barton, D E; Jenks, P; Pearson, J; Yates, J R
Abstract : A child with ambiguous genitalia, brought up phenotypically male, had a 46, XX/46, XY karyotype. At laparotomy, he had a left sided ovary and uterus, and a right sided scrotal testis. The 46, XX line made up 50% of cells in the blood and 90% of cells in a skin biopsy. There were no cytogenetic polymorphisms. Analysis of lymphocyte DNA with seven polymorphic DNA markers showed him to be chimaeric, with four, three, and two parental alleles at different loci. He had one paternal and one maternal X chromosome at the marker DXS1053. Based on our data, we would suggest that chimaerism arose as a result of postzygotic fusion of two embryos. We have shown by DNA polymorphisms the presence of autosomal chimaerism in a case of sex chromosome chimaerism, and indicated the usefulness of DNA polymorphisms in determining the origin of chimaerism.